GİRİŞİMCİLİKTE FONLAMA SORUNUNA YENİ BİR ÇÖZÜM ÖNERİSİ: KİTLESEL FONLAMANIN OLUMLU VE OLUMSUZ YÖNLERİ ÜZERİNE BİR İNCELEME* - Mumcu, Artür Yetvart; Ataman, Göksel (My University, 2021)
Girişimcilikte aşılması en güç zorluklardan biri olan girişim sermayesinin temini için günümüz teknolojilerinin sağladığı imkânların da yardımıyla alternatif çözümler geliştirilmektedir. Son 10 yıldır Türkiye’ de de kullanılmaya başlanan kitlesel fonlama da bu alternatif fon temin sistemlerinden biri olarak karşımıza çıkmaktadır. Ülke ekonomileri ve toplumların refah seviyesi için önemli bir unsur olan işletmelerin, kurulum aşamasında ihtiyaç duydukları fonun kitlelerden toplanması yöntemi ile uygulanan kitlesel fonlama, yazında da araştırmalara konu olmaktadır. Bu araştırmalar birçok farklı teoriler, yöntemler ve kültürler çerçevesinde gerçekleştirilmiştir. Yazında yer alan bu eserlerin ortak yönlerine odaklanılarak kitlesel fonlama için bir kavramsal çerçeve oluşturulmasına katkı sağlamak, araştırmamızın öncelikli amacını oluşturmuştur. Doktora tezinden türetilen bu araştırmada kitlesel fonlamada başarılı bir fonlamaya ulaşılabilmesi için gerekli hususların aydınlatılması amaçlanmıştır. Çalışmada kitlesel fonlama ile ilgili temel kaynak olarak ele alınan başlıca çalışmalardan oluşan ve Türkiye’de yayınlanmış 32, Uluslararası ise 62 araştırma içerik analizi yöntemi ile incelenmiştir. Bu inceleme sonucu kitlesel fonlamanın olumlu ve olumsuz yönleri ortaya konulmaya çalışılmıştır. Araştırma sonucunda, sistemin güven unsuru üzerinden çalışabildiği, yasal düzenlemeler ve uluslararası standartların da zaman içerisinde ortaya konularak bu risklerin azaltılabileceği görüşü doğmuştur.

Alternative solutions are developed with the help of the opportunities provided by today’s technologies for the provision of venture capital, which is one of the most difficult challenges in entrepreneurship. Crowdfunding, which has been used in our country for the last 10 years, is one of these alternative fund supply systems. Crowdfunding, which is an important element for the welfare of the countries’ economies and societies, is applied by collecting the funds needed by the enterprises during the establishment phase and has become the subject of research in the literature. In this study derived from the doctoral thesis, it is aimed to elucidate the necessary issues in order to achieve successful funding in crowdfunding. These researches have been carried out within the framework of many different theories, methods, and different cultures. Contributing to the creation of a conceptual framework for Crowdfunding by focusing on the common aspects of these researches in the literature has been the primary goal of our research. In our study, 33 researches from Turkey and 62 international researches considered as the main source of Crowdfunding, was examined by content analysis. The researches whose titles include the word “crowdfunding” on Google Scholar, T.C. Marmara University databases (Ebsco, Proquest etc.), Researchgate and Academia were chosen focusing on crowdfunding features which were repetitively used in these researches. As a result of this examination, the positive and negative aspects of Crowdfunding were revealed. Although Crowdfunding enables the realization of many social and economic initiatives, it was determined that project creators who are entrepreneur candidates may encounter many different problems in the collection of funds or in the following processes. As a result of the research, it was concluded that the system can operate on the basis of trust, and the risks can be reduced by introducing legal regulations and international standards over time. The fact that researches on the subject have been conducted 166 in many different countries created restrictions on revealing cultural differences. An increase in the number of local studies in Turkey and supporting the studies that have been using heuristic methods so far with quantitative methods, will contribute to the development of the conceptual frameworkof Crowdfunding. In addition, with the development of the legal infrastructure as well as scientific research, it will be possible for Crowdfunding to have a more reliable and widespread use area.
A NEW SOLUTION TO THE FUNDING PROBLEM IN ENTREPRENEURSHIP: A STUDY ON THE PROS AND CONS OF CROWDFUNDING
Keywords: Girişimcilik; Kitlesel Fonlama; Finans; Entrepreneurship; Crowdfunding; Finance; Covid-19